(untitled) (Journal of Mathematical Study, 2018)
In this paper,we prove that a unitary invariant strongly pseudoconvex complex Finsler metric is a complex Landsberg metric if and if only if it comes from a unitary invariant Hermitian metric. This implies that there does not exist unitary invariant complex Landsberg metric unless it comes from a unitary invariant Hermitian metric.